2013
DOI: 10.1007/s00431-013-2016-5
|View full text |Cite
|
Sign up to set email alerts
|

Bronchopulmonary dysplasia and neurodevelopmental outcome in extremely preterm neonates

Abstract: We tested the hypothesis that the use of supplemental oxygen (sO2) at discharge from the NICU in extremely preterm neonates is associated with a greater risk of neurodevelopmental impairment (NDI) at 18 months corrected gestational age (CGA) than the risk of NDI of those neonates discharged in room air. Four hundred twenty-four charts were retrospectively reviewed from infants born at <27 weeks and transferred to Nationwide Children’s Hospital from December 1, 2004 to June 14, 2010. Use of sO2 was evaluated on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 38 publications
1
49
1
2
Order By: Relevance
“…In a multicenter clinical study (1,12), only very-low-birth-weight infants with BPD requiring prolonged oxygen supplementation were at higher risk of poor long-term neurocognitive and academic performance, compared to premature infants exhibiting less severe BPD. These findings suggest that only severe BPD constitutes an independent risk factor for associated brain injury and poor long-term neurodevelopmental outcome in very-lowbirth-weight infants (1,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a multicenter clinical study (1,12), only very-low-birth-weight infants with BPD requiring prolonged oxygen supplementation were at higher risk of poor long-term neurocognitive and academic performance, compared to premature infants exhibiting less severe BPD. These findings suggest that only severe BPD constitutes an independent risk factor for associated brain injury and poor long-term neurodevelopmental outcome in very-lowbirth-weight infants (1,17).…”
Section: Discussionmentioning
confidence: 99%
“…The use of oxygen is critical for neonatal intensive care, and premature infants are especially vulnerable to oxygen toxicity due to the high possibility of exposure to supra-physiological oxygen concentrations during resuscitation and respiratory management, and a highly immature antioxidant defense mechanism. Besides the well-known toxic effects of hyperoxia on the developing lung, hyperoxia also leads to cell death in the developing white and grey matter of the brain, resulting in motor and cognitive deficits in premature infants (12)(13)(14)(15). In addition to the lung injury known to occur after prolonged exposure to hyperoxia (90% oxygen for 14 d), our data revealed simultaneous hyperoxic brain injury, shown by a retardation in brain weight gain, transiently increased carbonylated protein, reduced MBP, and an increased TUNEL-positive cells and caspase-3 expression, without changes in inflammatory cytokine levels, the number of activated microglia, and superoxide dismutase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Many infants with BPD also subsequently demonstrate significant neurodevelopmental impairments. 14 Although some reports imply that the burden of respiratory disease lies in the causative pathway to poor neurodevelopment, 13,57 a causal relationship remains unproven, and poor neurodevelopmental outcomes can develop in the absence of BPD. 8 …”
Section: Introductionmentioning
confidence: 99%
“…The current study performed on preterm Chinese infants showed HFOV to be associated with significantly lower rates of infant mortality and of BPD, indicating its beneficial effect on premature infants. BPD has been associated with poor neurodevelopmental outcome and was the strongest predictor of poor neurodevelopmental outcome in extremely preterm neonates receiving prolonged positive pressure support and having grade III-IV IVH [18] .…”
Section: Discussionmentioning
confidence: 99%